2008
DOI: 10.1093/aob/mcn113
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Local Size Hierarchy Causes Regular Spacing of Trees in an Even-aged Abies Forest: Analyses Using Spatial Autocorrelation and the Mark Correlation Function

Abstract: This is the first study to detect local size hierarchies as a prelude to regular spacing using the mark correlation function. The results confirm that use of the mark correlation function together with the spatial autocorrelation function is an effective tool to analyse the development of a local size hierarchy of trees in a forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 30 publications
5
52
0
Order By: Relevance
“…In other ecological situations also positive correlation of tree heights is possible, for example in forests with trees of different age, where young trees appear in clusters. An interesting example is discussed in Suzuki et al (2008). In an even-aged Abies forests in Japan they observed that the correlation of tree heights changed from positive to "no correlation" during the early stage of stand development, whereas in the older stages of forest development it was changed again from "no correlation" to negative one.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In other ecological situations also positive correlation of tree heights is possible, for example in forests with trees of different age, where young trees appear in clusters. An interesting example is discussed in Suzuki et al (2008). In an even-aged Abies forests in Japan they observed that the correlation of tree heights changed from positive to "no correlation" during the early stage of stand development, whereas in the older stages of forest development it was changed again from "no correlation" to negative one.…”
Section: Discussionmentioning
confidence: 97%
“…Applications of marked point process statistics in forest sciences can be found in Penttinen et al (1992), Wälder and Stoyan (1996), Degenhardt (1999), Stoyan and Penttinen (2000), Gavrikov and Stoyan (1995), Pommerening (2002), Kint et al (2003), Wälder and Wälder (2008), Suzuki et al (2008), Law et al (2009, Ledo et al (2011), Pommerening andSärkkä (2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…plants, trees) and environmental factors on their sizes. It characterizes squared differences between marks (m) of pairs of points within the distance of r under the condition that there are points at locations x and x + r (Stoyan and Penttinen 2000;Stoyan and Wälder 2000;Suzuki et al 2008;Gonçalves et al 2011;Pommerening and Särkkä 2013):…”
Section: Marks and Mark Hypothesis Testingmentioning
confidence: 99%
“…Examples of applications of different functions mentioned above can be found in Kuuluvainen et al (1996), Kenkel (1997), Rozas (2003), Getzin et al (2006), Wiegand et al (2007), Illian et al (2008), Suzuki et al (2008), Wälder and Wälder (2008), Gray and He (2009), Nuske et al (2009), Picard et al (2009, Rozas et al (2009), Zhang et al (2010, Ledo et al (2011);Nanami et al (2011), Iszkuło et al (2012 and Pommerening et al (2013). …”
Section: Marks and Mark Hypothesis Testingmentioning
confidence: 99%